Effects of Veterinary Medicines in the Environment - Crane, Mark (CRC Press, 2009)
This timely book examines veterinary medicines, an increasingly important issue for environmental regulators. It brings together more than 30 experts from eight countries with expertise in risk assessment, environmental toxicology and chemistry, and environmental policy and business sectors. The text discusses pathways to the environment, the range and point of diffusion, risk assessment and management, and exposure and effects assessment in the terrestrial and aquatic environments. It reviews classes of veterinary drugs and current regulations, identifies environmental fate of the drugs, and assesses the use of read-across, QSAR, and other modeling approaches.